2022
DOI: 10.3389/fgene.2022.997780
|View full text |Cite
|
Sign up to set email alerts
|

tRNA derived small RNAs—Small players with big roles

Abstract: In the past 2 decades, small non-coding RNAs derived from tRNA (tsRNAs or tRNA derived fragments; tRFs) have emerged as new powerful players in the field of small RNA mediated regulation of gene expression, translation, and epigenetic control. tRFs have been identified from evolutionarily divergent organisms from Archaea, the higher plants, to humans. Recent studies have confirmed their roles in cancers and other metabolic disorders in humans and experimental models. They have been implicated in biotic and abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 203 publications
0
5
0
Order By: Relevance
“…With advances in next-generation sequencing technology, numerous sncRNAs, including microRNAs, circular, p-element-induced wimpy testis-interacting and small nucleolar RNAs and tRNAs, have been confirmed to serve significant roles in a variety of diseases (27). Recently, tRNA-derived small fragments, called tsRNAs, have attracted considerable attention (28)(29)(30). The two types of tsRNA, tRNA-derived stress-induced RNA (tiRNA) and tRFs, are classified according to the different cleavage positions of the precursor or mature tRNA transcript (31).…”
Section: Discussionmentioning
confidence: 99%
“…With advances in next-generation sequencing technology, numerous sncRNAs, including microRNAs, circular, p-element-induced wimpy testis-interacting and small nucleolar RNAs and tRNAs, have been confirmed to serve significant roles in a variety of diseases (27). Recently, tRNA-derived small fragments, called tsRNAs, have attracted considerable attention (28)(29)(30). The two types of tsRNA, tRNA-derived stress-induced RNA (tiRNA) and tRFs, are classified according to the different cleavage positions of the precursor or mature tRNA transcript (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions of tsRNAs have not yet been elucidated, an increasing number of studies have shown that tsRNAs play their biological functions in multiple regulatory mechanism, including epigenetic regulation, transcriptional or post-transcriptional regulation, and translation regulation [ 66 ] (Fig. 3 ).…”
Section: Discovery Biogenesis and Regulatory Mechanism Of Tsrnasmentioning
confidence: 99%
“…tRFs play pivotal roles in regulating gene expression, acting in a miRNA-like manner and affecting numerous biological processes, including cell proliferation, migration and apoptosis. 15,16 Interestingly, a substantial proportion of tRFs arises from mitochondrial tRNAs (mt-tRNAs) and are actively implicated in tumorigenesis and cancer progression, primarily through their role in perturbing translation and mitochondrial metabolism. 17,18 Herein, we have investigated tRF profiles in association with MM and benign disease states (MGUS/sMM), aiming to reveal potential MM-related tRFs of clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Although tRFs were considered as by‐products of tRNA metabolism, recent studies and high‐throughput sequencing techniques have brought them to RNA biology spotlight regarding their distinct evolutionary conserved sequences and high abundance in various cell types. tRFs play pivotal roles in regulating gene expression, acting in a miRNA‐like manner and affecting numerous biological processes, including cell proliferation, migration and apoptosis 15,16 . Interestingly, a substantial proportion of tRFs arises from mitochondrial tRNAs (mt‐tRNAs) and are actively implicated in tumorigenesis and cancer progression, primarily through their role in perturbing translation and mitochondrial metabolism 17,18 …”
Section: Introductionmentioning
confidence: 99%